Pelatihan Instalisasi Windows Pada Siswa dan Guru SMA Negeri 3 Kota Pagar Alam - Wita Hariani (Program Studi Administrasi Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Bengkulu, 2021)
Most students and teachers in Pagar Alam City know a lot about the basic concepts of installing a computer operating system as a support for learning, the role of computers is very important, especially because early students and teachers have to meet many computer subjects who must have a good understanding of programming logics, so that installation training becomes very important because generally teachers and early students are only able to operate it, without understanding what tips and tricks if there are things or things that must be maintained from the computer system, this training is the first understanding for teachers and students. To increase knowledge in this maintenance, training participants are given basic knowledge and skills about; Preparation Make the installation of software and what devices must be provided, a computer operating system installation guide and a tutorial for making an installation system with Windows. Located at the Computer LAB of SMA Negeri 3 Pagar Alam City with a total of 30 participants, the training was held on: 05-03-2021. The method used is the lecture method, practice, question and answer, discussion and practice. Based on the results of the evaluation, it turned out that in general there was an increase in the knowledge of the trainees. It is also hoped that from this activity students can also pass on the knowledge that has been obtained to other students and teachers